Climate change and food systems: Transforming food systems for adaptation, mitigation, and resilience - Swinnen, Johan; Arndt, Channing; Vos, Rob (International Food Policy Research Institute, 2022)
Climate change is a growing threat to our food systems, with grim implications for food and nutrition security, livelihoods, and overall well-being, especially for poor and vulnerable people around the world. The imperative for urgent action on climate change — both to achieve the major emissions reductions needed to limit global warming and to increase adaptive capacity and resilience of food systems — is drawing global attention.